2016
DOI: 10.1073/pnas.1607536113
|View full text |Cite
|
Sign up to set email alerts
|

Piperine’s mitigation of obesity and diabetes can be explained by its up-regulation of the metabolic rate of resting muscle

Abstract: We identify a target for treating obesity and type 2 diabetes, the consumption of calories by an increase in the metabolic rate of resting skeletal muscle. The metabolic rate of skeletal muscle can be increased by shifting myosin heads from the super-relaxed state (SRX), with a low ATPase activity, to a disordered relaxed state (DRX), with a higher ATPase activity. The shift of myosin heads was detected by a change in fluorescent intensity of a probe attached to the myosin regulatory light chain in skinned ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 54 publications
(74 reference statements)
7
48
2
Order By: Relevance
“…2B; Table 1). These time constants are in remarkable agreement with fiber-level measurements in rabbit soleus muscle (5,12), suggesting that the longer lifetime population is reflective of SRX myosin in the myofibril preparation.…”
Section: Main Textsupporting
confidence: 80%
“…2B; Table 1). These time constants are in remarkable agreement with fiber-level measurements in rabbit soleus muscle (5,12), suggesting that the longer lifetime population is reflective of SRX myosin in the myofibril preparation.…”
Section: Main Textsupporting
confidence: 80%
“…To supplement the approach of looking for small molecules like OM and BS that perturb the actin‐myosin ATPase cycle as determined with soluble myosin fragments that do not form filaments, it might be possible to design or screen for molecules that perturb the regulatory state of the thick filament without large effects on the actin‐myosin ATPase (Nogara et al . ). In principle, and in contrast with OM, such molecules could be simple activators without competing inhibitory effects, which might facilitate the selection of a therapeutic dose.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study found that piperine could attenuate weight gain in rodents (BrahmaNaidu et al, 2014 ), and the beneficial effect of piperine was associated with the up-regulation of the metabolic rate of resting muscle (Nogara et al, 2016 ). In the metabolic syndrome model, piperine reduced ventricular wall thickness and attenuated cardiac collagen deposition in rats fed a high-fat diet (Diwan et al, 2013 ).…”
Section: Anti-fibrotic Effect Of Polyphenols On Cardiac Fibrosismentioning
confidence: 99%